Hacia el abandono de la mención de la causa en la conformación definitoria del contrato - Luna Serrano, Agustín (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Dissapearence of the cause in the legal definition of contract observable in some European civil code and in projects for the unification of contract law and the posible or indirect permanence of its significance.
Keywords: Cause; consideration; dissapearence of the cause in proposals for the unification of contract law; its potential persistence